Perancangan Sistem Automatic Transfer Switch Berbasis ESP32 Terintegrasi Scada Dan IoT Pada PLTS - Muhammad Hafiizh Yusra; Akhmad Wahyu Dani (Jurnal Teknologi Elektro, 2026)
Solar energy is one of the most abundant renewable energy sources in Indonesia and holds great potential to be utilized as an alternative source of electricity. One of the technologies used to harness this energy is the Solar Power Plant (PLTS), which can serve as a backup power source in electrical systems. The use of PLTS not only supports the reduction of dependence on fossil fuels but also contributes to electricity supply in remote areas. However, to optimize the utilization of solar energy as a backup source, a reliable and automatic power switching system is required to ensure the continuity of power supply.This study designs and implements an Automatic Transfer Switch (ATS) system based on ESP32, integrated with Supervisory Control and Data Acquisition (SCADA) and Internet of Things (IoT) technologies. The system enables automatic switching from the main power source, namely the PLN power grid, to the backup source, namely PLTS, in the event of a power failure or disruption in the PLN supply. Furthermore, the system allows for remote monitoring and control via IoT platforms and displays real-time data to facilitate analysis and decision-making. The implementation results show that the ATS system is able to quickly detect disturbances in the main source and automatically switch to the solar power plant with a stable and accurate response. Tests show a stable supply voltage at 4.97VDC, the switching system runs without failure, and all components—both hardware and software—function in an integrated manner. Data communication using the Modbus TCP/IP and Blynk TCP/IP protocols runs smoothly, and all electrical parameters can be monitored synchronously via SCADA and the Blynk application in real-time. With successful testing in all aspects, this system has proven reliable and feasible to be implemented as a renewable energy-based hybrid power supply management solution with SCADA and IoT support..